Diabetes mellitus, CYP2C19 genotype, and response to escalating doses of clopidogrel - Carreras, Edward T.; Hochholzer, Willibald; Frelinger, Andrew L., III; Nordio, Francesco; O’Donoghue, Michelle L.; Wiviott, Stephen D.; Angiolillo, Dominick J.; Michelson, Alan D.; Sabatine, Marc S.; Mega, Jessica L. (Thrombosis and Haemostasis, 2016)
Both diabetes mellitus (DM) and carriage of the CYP2C19*2 allele are associated with a reduced response to clopidogrel. The relative contributions of these factors and whether higher clopidogrel doses can overcome both factors remain unknown. The objective of this study was to test the ability of clopidogrel doses up to 300 mg daily to decrease platelet reactivity in patients with DM and/or CYP2C19*2. ELEVATE-TIMI 56 randomised 333 patients with coronary artery disease to different maintenance doses of clopidogrel in four treatment periods, each lasting approximately 14 days. On-treatment platelet reactivity was compared between patients stratified by DM, CYP2C19*2 status and clopidogrel dose. Both DM and CYP2C19*2 were independently associated with elevated on-treatment platelet reactivity with clopidogrel 75 mg daily (p<0.0001 for each). With 75 mg, mean on-treatment PRU was progressively higher (p trend <0.001) when evaluating patients: with neither DM nor CYP2C19*2 (150.7; 95 % CI 140.5–162.6), with only DM (187.2; 95 % CI, 171.3–206.9), with only CYP2C19*2 (227.9; 95 % CI, 205.1–250.8), and with both DM and CYP2C19*2 (239.9; 95 % CI, 209.7–270.1). Notably, with 75 mg, patients with only CYP2C19*2 had higher ontreatment platelet reactivity than those with only DM (p=0.0068). To achieve on-treatment platelet reactivity similar to that seen with clopidogrel 75 mg in patients with neither DM nor CYP2C19*2, the following doses were required: 150 mg with only DM, 225 mg with only CYP2C19*2, and 300 mg with both DM and CYP2C19*2. Patients with both DM and CYP2C19*2 required a four-fold increase in clopidogrel maintenance dose as compared to patients without these factors to achieve a similar antiplatelet response.
Keywords: Diabetes mellitus; ischaemic heart disease; platelet pharmacology; polymorphisms